LAW, SOCIAL MEDIA, AND THE KARAOKE BUSINESS - Putri, Elinda Rizky; Octarina, Nynda Fatmawati (JILPR Journal Indonesia Law and Policy Review, 2024)
Intellectual property law, particularly copyright law, is a significant challenge for karaoke businesses. The necessity of obtaining proper music licenses is well-understood, but the complexities and costs involved often lead to gaps in compliance. Local regulations, including zoning laws, noise ordinances, and alcohol licensing, further complicate the legal landscape for karaoke operators. Non-compliance with these laws can result in severe penalties, including fines, legal disputes, and potential business closures. Social media has emerged as an essential tool for marketing and customer engagement in the karaoke industry. Platforms like Facebook, Instagram, and TikTok enable businesses to reach a broader audience and create interactive experiences that enhance customer loyalty. However, the use of copyrighted music in social media posts poses significant legal risks. While social media offers opportunities for growth, businesses must navigate these platforms carefully to avoid copyright infringement and other legal challenges. Managing online reputations is critical in the age of social media, where negative reviews or viral posts can significantly impact a business's image. Proactive strategies for handling customer feedback and maintaining a positive online presence are essential for mitigating reputational risks. The regulatory environment for karaoke businesses is evolving, with stricter enforcement of copyright laws and changing social media policies. Businesses must stay informed and adapt to these changes to ensure continued compliance and operational success. Karaoke businesses should prioritize legal education and seek expert guidance to navigate the complexities of copyright law and other regulatory requirements effectively. Clear social media policies that address the use of copyrighted material and customer interactions are vital for minimizing legal risks and maximizing the benefits of digital marketing. Implementing robust reputation management strategies, including prompt responses to online reviews and engagement with customers, can help maintain a positive public image and reduce the impact of negative feedback. Businesses should monitor changes in copyright enforcement and social media regulations, adapting their practices accordingly. Forming partnerships with music rights organizations or utilizing technology solutions can streamline compliance efforts.